Characterization of food waste in Grizzly Dining Hall at Georgia Gwinnett College: A critical step toward sustainable food waste management - Ramata Sissoko Cisse; Fatima Sarahi Aguilar; Sochi Bryan Ezenagu; Mahamane Saliou Cisse; Amadou Niang (Heliyon)
This project investigated the generation and characterization of post-service food waste at Georgia Gwinnett College dining hall from Spring 2022 to Spring 2023. In Spring 2022, for three weeks, twice a week, a total of 115.08 kg of post-service food waste was collected by cafeteria workers. In Fall 2022, for 1 h, twice a week, for five weeks, post-service food waste was collected directly from visitors, sorted, and immediately weighed. During the first half of the Fall 2022 collection, 58.17 kg of food waste was collected and sorted into three categories, consisting of 17.90 % disposable cutlery, 20.46 % fruits and vegetables, and 61.64 % mixed food. During the second half of the Fall 2022 collection, 69.13 kg of food waste collected was composed of 12.84 % disposable cutlery, 23.59 % fruits and vegetables, and the mixed food subcategorized was composed of 11.27 % starch, 39.45 % grain, and 12.84 % meat and eggs. Finally, in Spring 2023, for six consecutive days, the waste was collected as previously but during the entire day and sorted. The average daily waste amounted to 113.41 kg, consisting of 18.20 % disposable cutlery, 16.62 % fruits and vegetables, 9.47 % starch, 33.26 % grain, and 22.45 % meat and eggs. Out of the food categories collected, grains constitute the largest source of food waste by weight. The study indicated that, on average, 140 g of food waste was produced per student per day during Spring 2023. The result of this study represents an opportunity for the college to identify the types and amounts of food waste generated at the cafeteria and to plan a better waste management system.